The Examination of Prospective Chemistry and Physics Teachers' Cognitive Structure Related to Quantum Numbers - Senar Temel; Özgür Özcan (Anı Publishing, 2020)
This study firstly aimed to analyse prospective chemistry and physics teachers' comprehension levels to quantum numbers. Secondly, the study analysed the changes in both groups of prospective teachers' levels of comprehending quantum numbers. In this context, qualitative research method was used and purposeful sampling method was employed in the selection of the participants in this study. 8 prospective chemistry and 9 prospective physics teachers were included in the study. The prospective teachers' responses to the seven open-ended questions were analysed separately by the two researchers according the classification made by Abraham, Grybowsky, Renner and Marek (1992). First, prospective chemistry and physics teachers' level of understanding quantum numbers was determined. Then, variability in their levels of understanding was examined. In addition to that, prospective teachers' probable misconceptions/alternative concepts/wrong concepts and deficient knowledge was also determined. It was concluded that prospective teachers in general had wrong concepts in addition to partial understanding the subject. It was also found that there were considerable changes in their comprehension levels. In this context, the nature of prospective teachers' understanding of quantum numbers was discussed in details.